Artemia with Synbiotics Enrichment Improves Resistance Against Vibrio parahaemolyticus AHPND of Litopenaeus vannamei Larvae - Ervia Yudiati; Zaenal Arifin; Adi Santoso; Jelita Rahma Hidayati; Rabia Alghazeer; Nuril Azhar (Universitas Diponegoro, 2023)
Shrimp, a high-protein food commodity, is one of the world's fastest-growing food-producing sectors. The present research aimed to find out the survival and growth of Litopenaues vannamei Post Larva (PL) and the resistance against VpAHND and stress salinity. 1500 PL were reared to two sets of experiments at the density of 50 PL. L-1. The first set is purposed to determine the PL growth, resistance to Vibrio paramaemolyticus AHPND challenge and stress salinity. The second set is purposed to determine the survival rate. A Completely randomized design (CRD) with five treatments and three replications was conducted. The treatments are Artemia enrichment with different Alginate doses and probiotics (400, 600, 800 ppm Alg+pro), probiotics (Pro), and control without any synbiotics addition. PL was reared in 14 days. The survival rate, and weight gain were calculated. At the end of the experiment, 10 PL was challenged against VpAHPND at 1 x 107 CFU mL-1by immersion methods. Twenty PL was exposed to stress salinity and shocked from 25 ppt to 0 ppt. The best survival rate ((78±2%), and tolerance to osmotic stress was reached at PL fed on a combination of alginate and FNCC-002 Lactobacillus bulgaricus probiotics (p<0.05). PL fed on Artemia enriched probiotics reached the highest resistance to severe VpAHNPD. The weight gain among treatments is similar. It can be concluded that synbiotics of alginate as prebiotics and FNCC-004 probiotics work synergically and this might be interrelated with immune response.